Women's Stereotypes in the Implementation of Reproductive and Productive Roles in Women Farmers' Households - Wiji Tuhu Utami; Retno Setyowati; Sugihardjo Sugihardjo (HUMANISMA : Journal of Gender Studies, 2021)
The role of the wife has an essential contribution in the household as the smallest unit in household life. Stereotypes are specific labels attached to women in their roles as wives, mothers, and in society. The research aims to analyze stereotypes among women who work as processed food producers to implement household gender roles. The method in this research uses descriptive qualitative. The study results show that the pattern of household gender relations for Ngudi Rejeki Women Farmer Group members is equal. Household problems may resolve on their own or require discussion. Ngudi Rejeki Women Farmer Group members work as a processed food producer with a processed product entity made from Moringa leaves. The stereotype of responsibility is held husband as the family head and the housewife as the wife's prominent role, in the household function the husband as the primary breadwinner and the wife as the additional breadwinner. In implementing the reproductive role, the wife has a more prominent role and the husband only a helping hand. Peranan istri memiliki berkontribusi penting dalam rumah tangga sebagai unit terkecil dalam kehidupan rumah tangga. Stereotip merupakan pelabelan tertentu yang melekat pada perempuan dalam perannya sebagai istri, ibu, dan pada masyarakat. Penelitian bertujuan untuk menganalisis stereotip pada perempuan produsen makanan olahan dalam pelaksanaan peran gender rumah tangga. Metode dalam penelitian ini menggunakan deskriptif kualitatif. Hasil penelitian menunjukkan bahwa pola relasi gender rumah tangga anggota KWT Ngudi Rejeki ke arah setara. Permasalahan rumah tangga dapat selesai dengan sendirinya atau memerlukan pembahasan. Anggota KWT Ngudi Rejeki bekerja sebagai produsen makanan olahan dengan entitas produk olahan berbahan dasar daun kelor. Stereotip dalam hal tanggung jawab yaitu kepala keluarga dikonstruksikan sebagai tanggung jawab suami dan ibu rumah tangga menjadi tanggung jawab istri, pada fungsi rumah tangga dikonstruksikan suami sebagai pencari nafkah utama dan istri sebagai pencari nafkah tambahan, dan pada pelaksanaan peran reproduktif mengonstruksikan istri memiliki peran yang lebih utama dan suami sekedar membantu.